2013
DOI: 10.1155/2013/609395
|View full text |Cite
|
Sign up to set email alerts
|

Th17-Associated Cytokines as a Therapeutic Target for Steroid-Insensitive Asthma

Abstract: Steroid-insensitive asthma is an infrequent but problematic airway disease that presents with persistent symptoms, airflow limitation, or recurrent exacerbations even when treated with steroid-based therapies. Because of unsatisfactory results obtained from currently available therapies for steroid-insensitive asthma, a better understanding of its pathogenesis and the development of new targeted molecular therapies are warranted. Recent studies indicated that levels of interleukin (IL)-17 are increased and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 95 publications
1
38
0
Order By: Relevance
“…Our results demonstrating low sensitivity of Th 17 cells, both in vivo and in vitro, to the inhibitory action of MP (13,14.19) have been later confirmed by findings that T lymphocytes derived from MS patients with an enhanced Th17-like phenotype are less sensitive to hydrocortisone inhibition (23) and severe forms of allergic asthma associated with Th17 response are poorly controlled by corticosteroids (24). Moreover, it has been recently shown that not only Th17 cells are refractory to the inhibitory actions of steroids but also that these cells are actively and specifically selected for within mixed T cell cultures upon exposure to steroids (25).…”
Section: Resultssupporting
confidence: 68%
“…Our results demonstrating low sensitivity of Th 17 cells, both in vivo and in vitro, to the inhibitory action of MP (13,14.19) have been later confirmed by findings that T lymphocytes derived from MS patients with an enhanced Th17-like phenotype are less sensitive to hydrocortisone inhibition (23) and severe forms of allergic asthma associated with Th17 response are poorly controlled by corticosteroids (24). Moreover, it has been recently shown that not only Th17 cells are refractory to the inhibitory actions of steroids but also that these cells are actively and specifically selected for within mixed T cell cultures upon exposure to steroids (25).…”
Section: Resultssupporting
confidence: 68%
“…There has been an increase in the literature of evidence supporting a role of the IL-17/neutrophil axis in more severe and glucocorticoid-resistant subsets of patients (1, 3, 30, 31). We report here that human primary Th17 cells and mouse in vitro differentiated Th17 cells do not undergo glucocorticoid-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, a special focus on screening of treatments that not only control symptoms of asthma, but also modify T cell function is recommended. Various lines of evidence indicate that T helper 17 (Th17) is a third distinct lineage of CD4 þ T cells independent of Th1 and Th2 cell types with its signature cytokine IL-17A, and have crucial role in asthma pathogenesis (Durrant and Metzger, 2010;Stelmaszczyk-Emmel et al, 2013) and were considered to be closely associated with refractory asthma (Cosmi et al, 2011;Morishima et al, 2013). Regulatory T (Treg) cells is another subtype of CD4 þ T cells with general immunosuppressive effect, and played considerable role in controlling allergic diseases such as asthma (Ray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%